(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
This article has the general objective of evaluating two library automation software, the proprietary software Pergamum and the free software Biblivre, using their websites as an investigation tool. The research is defined as exploratory and descriptive. The data collection instrument was a form used to identify the functionalities provided by each software according to the information available on their websites. It was possible to conclude that the library automation market is rich in software and serves the public that has the resources to invest in automation to those looking for free alternatives. It is also concluded that both evaluated software have a considerable set of functionalities capable of fully meeting the demands for library collection management, which contributes to the great prominence and adoption that Pergamum and Biblivre have in the library scenario. different types of libraries.